Variational Formulation for Quaternionic Quantum Mechanics - de Melo, C. A. M. [UNESP]; Pimentel, B. M. [UNESP] (Birkhauser Verlag Ag, 2010)
A quaternionic version of Quantum Mechanics is constructed using the Schwinger's formulation based on measurements and a Variational Principle. Commutation relations and evolution equations are provided, and the results are compared with other formulations.
Keywords: Quaternionic quantum mechanics; variational principle